Economics Of Sorghum Production, Consumption And Trade In Sudan (1990 - 2020) - Elgilany A. Ahmed; Fatima Rahma Mohammed (Journal of Agricultural Extension Management, 2026)
This paper focuses on a set of high-potential of sorghum commodity in Sudan. Sorghum is considered as one of the most important calorie source in the Sudanese diet, future key source of sustainable farming systems and the national economy of Sudan. The paper analyzes sorghum by evaluating its production, consumption and trade trends for a 10-years period (term) for the last three decades (1990 to 2021), and indicates the projections for production, consumption and demand up to 2030. The paper depended mainly on secondary data collected from relevant sources such as the annual statistics of the Central Ministries of Agriculture and Forests for various years. The findings have illustrated that the production of sorghum shows a high annual growth rate during the first (1990s) and the third terms (2010s) in the rain-fed sector. It is clear that, total sorghum consumption in the Sudan rose at an average annual rate lower than the production rate for the whole period of the study. Sorghum is mainly grown for local consumption by small scale holders (60% of quantity produced) in main producing areas, particularly in traditional rain-fed farming, in semi-mechanized and in irrigated agriculture. The overall trend of the most exports during 1990 -2020 is fluctuated The period 2000s was the period of oil export from Sudan which was the major source of foreign currency to the government neglecting traditional agricultural exports and the impact was deterioration on agricultural export quantities.